History of Islamic libraries in India during the period of Islamic rule (392-1473 AH) | تاريخ المكتبات الإسلامية في بلاد الهند خلال فترة الحكم الإسلامي (392-1473 هـ) - Mouqbil | مقبل, Reda Said | رضا سعيد (King Fahad National Library | مكتبة الملك فهد الوطنية, 2023)
Libraries constitute an integral part of the history and civilization of Islam. They have played a distinguished role in spreading knowledge and culture among Muslims. It can be said that Islamic civilization is a civilization of books and libraries. There is no civilization without knowledge, and no knowledge without books and libraries. Islam in India has a rich history that lasted more than eight centuries, during which Muslims established one of the finest civilisations. However, most of those who wrote about the history of Islamic libraries ignored libraries in India, because this country is far from the center of the Islamic world, in addition to the difficulty of that study. Due to the lack and dispersion of information in many sources and references related to India. Perhaps this represents an incentive to reveal the office renaissance that... This country witnessed it during the era of Islamic rule | تُشكل المكتبات جزءا لًا يتجزأ من تاريخ الإسلام وحضارته، فقد كان لها دورها المتميز في نشر المعرفة والثقافة بين المسلمين. ويمكن القول بأن الحضارة الإسلامية حضارة كتب ومكتبات، فلا حضارة بدون علم، ولًا علم بدون كتب ومكتبات. وللإسلام في بلاد الهند تاريخ حافل استمر أكثر من ثمانية قرون، أسس المسلمون خلالها حضارة من أرقى الحضارات، إلًا ُ أن جل الذين كتبوا عن تاريخ المكتبات الإسلامية أغفلوا المكتبات في الهند، بسبب أن هذه البلاد بعيدة عن مركز العالم الإسلامي، بالإضافة إلى صعوبة تلك الدراسة لقلة المعلومات وتشتُّ ِتها في كثير من المصادر والمراجع المتعلقة بالهند. ولعل ذلك يُمثل حافزا للكشف عن النهضة المكتبية التي شهدتها تلك البلاد في حقبة الحكم الإسلامي